Shifts from phosphorus to nitrogen limitations of microbial metabolism with the forest development of Phoebe bournei plantations - Zhengyang Zheng; Bowen Min; Zehao Li; Fanghai Luo; Hechuan Wang; Ying Zhang; Ziqiao Yang; Hanbin Wu; Lili Yang; Gongxiu He; Lei Lv; Li Ji (Applied Soil Ecology, 2026)

Mechanochemical elimination of antibiotics and antibiotic resistance genes using PAN@BTO piezoelectric composite - Ling Yu; Mengxiao Liu; Hanbin Wu; Li Zeng; Yang Yu (Journal of Environmental Chemical Engineering, 2026)

Elimination of antibiotic resistance genes by three-dimensional electrochemical activation of peroxymonosulfate using Co3O4@BTO particles - Mengxiao Liu; Li Zeng; Hanbin Wu; Yiyang Xu; Yang Yu (Journal of Environmental Chemical Engineering, 2026)

Electrohydrodynamic jet printing and controllable heat transformation for morphology-tailored platinum nanowires with ultra-high length-diameter ratio - Fan Zhang; Tong Hao; Lujing Sun; Mingyang Kong; Xinghui Qu; Haigang Wang; Hanbin Wang; Zhe Yang; Zhipeng Zhao; Junsheng Liang (Chemical Engineering Journal, 2026)

Efficacy and Safety of Probiotics, Prebiotics and Synbiotics for the Treatment of Functional Constipation in Children: Systematic Review and Network Meta-analysis - Cui Liang; Xinxin Deng; Hanbin Wang; Xiaoye Hu; Lu Cui; Jiayi Huang; Meng Xu; Liangying Hou; Shenggang Xu; Liying Zhou; Xue Shang; Kehu Yang; et al. (Probiotics and Antimicrobial Proteins, 2026)

Corrigendum to “Study on the enhancement of wave energy capture performance of Savonius hydrokinetic turbines using rear-mounted curved deflectors” [Ocean Engineering 353 1 (2026) 124622] - Fengshen Li; Weixin Yang; Renwei Ji; Claes Eskilsson; Hanbin Gu; Congjie Ren; Ruiyin Song (Ocean Engineering, 2026)

Study on the enhancement of wave energy capture performance of Savonius hydrokinetic turbines using rear-mounted curved deflectors - Fengshen Li; Weixin Yang; Renwei Ji; Claes Eskilsson; Hanbin Gu; Congjie Ren; Ruiyin Song (Ocean Engineering, 2026)

Singlet oxygen-dominated dye degradation by cobalt-functionalized ceramic hollow fiber membrane via peroxymonosulfate activation - Li Zeng; Hanbin Wu; Yiyang Xu; J. Paul Chen; Yiqiao Xie; Yang Yu (Journal of Water Process Engineering, 2026)

Behavior and evaluation of the lap splice for steel-FRP composite bars embedded in concrete beams - Yi Zheng; Zeyang Sun; Liuzhen Yao; Xin Wang; Yang Wei; Hanbin Ge (Engineering Structures, 2026)

Differential electric field homogenization postponed dendrite formation of zinc anodes at limiting current for long-life aqueous zinc batteries - Yin Yang; Xin Chen; Jingying Li; Jia Yao; Yi Gan; Junjie Zheng; Luyang Ge; Lin Lv; Li Tao; Jun Zhang; Hanbin Wang; Hao Wang; et al. (Chemical Engineering Journal, 2025)

A novel polypeptide from stony coral Goniopora columna inhibits thrombosis by interfering with the contact-kinin pathway - Qian Chen; Congshuang Deng; Xiaoshan Huang; Kaixun Cao; Hanbin Chen; Yang Chen; Mehwish Khalid; Qiuyue Xu; Qiumin Lu; Ziyi Wang; Aili Wang; Ren Lai (Archives of Toxicology, 2025)

Interface molecular reconstruction with scarcity active factor for long-life aqueous zinc batteries at thermal environment - Xin Chen; Yin Yang; Runzhi Liang; Junjie Zheng; Jia Yao; Jingying Li; Yi Gan; Xin Liu; Xiaodong Liang; Ze Wang; Qin Liu; Lin Lv; et al. (Chemical Engineering Journal, 2025)

Interface engineering of plant oil body for an innovative food ingredient: A review - Ruizhi Yang; Haotian Deng; Yadong Zhao; Hanbin Lin; Yan Song; Luping Zhao; Wenhua Miao; Bin Zheng (Trends in Food Science & Technology, 2025)

Automatic crack detection on concrete and asphalt surfaces using semantic segmentation network with hierarchical Transformer - Hubing Li; Haowei Zhang; Hong Zhu; Kang Gao; Hanbin Liang; Jiangjin Yang (Engineering Structures, 2024)

Husband smoking is associated with Wife's thyrotropin abnormality: A population-based cohort study among Chinese reproductive-aged women - Siyu Wu; Ying Yang; Yunzhi Chen; Wenlu Xie; Jiaxin Huang; Meiya Liu; Youhong Liu; Die Xu; Xinyi Lyu; Hanbin Wu; Jueming Lei; Chuanyu Zhao; et al. (International Journal of Hygiene and Environmental Health, 2024)

Spatiotemporal distribution, mobilization kinetics and risk assessment of nickel in sediments of Lake Taihu, China - Yijun Song; Hanbin Zhao; Xin Ma; Cai Li; Liyuan Yang; Shiming Ding (Journal of Soils and Sediments, 2024)

AIEgens-enhanced rapid sensitive immunofluorescent assay for SARS-CoV-2 with digital microfluidics - Yuping Zeng; Xiangyu Gan; Zhourui Xu; Xiaoxiang Hu; Chenxuan Hu; Hanbin Ma; Hangjia Tu; Bao Chai; Chengbin Yang; Siyi Hu; Yujuan Chai (Analytica Chimica Acta, 2024)

Simultaneous regeneration of activated carbon and removal of adsorbed atrazine by ozonation process: From laboratory scale to pilot studies - Shan Liu; Zhonglin Chen; Yang Shen; Hao Chen; Zhenxin Li; Liming Cai; Hanbin Yang; Congshi Zhu; Jimin Shen; Jing Kang; Pengwei Yan (Water Research, 2024)

Seasonal variations in spatial distribution, mobilization kinetic and toxicity risk of arsenic in sediments of Lake Taihu, China - Shuhang Wang; Shiming Ding; Hanbin Zhao; Musong Chen; Dianhai Yang; Cai Li (Journal of Hazardous Materials, 2024)

Microgel-enhanced thermal-sensitive hydrogel electrolyte enables active heat management, controllable energy storage and mechanical flexibility of supercapacitors - Yang Gao; Hongwei Zhou; Bohui Zheng; Zhao Wang; Guoxu Zhao; Hongli Zhang; Hanbin Liu; Xilang Jin; Weixing Chen; Aijie Ma; Yuanpeng Wu (Chemical Engineering Journal, 2023)

Study on air escape in submerging process of multi-box girder attacked by flood - Wanli Yang; Yuxuan Liu; Yuankang Yang; Dewen Liu; Jiejun Ning; Yuzhi Zhang; Hanbin Yang (Ocean Engineering, 2023)

The effect of rotational degree and routine activity on the risk of collapse in transtrochanteric rotational osteotomy for osteonecrosis of the femoral head—a finite element analysis - Pusheng Xie; Yuping Deng; Jinchuan Tan; Mian Wang; Yang Yang; Hanbin Ouyang; Wenhua Huang (Medical & Biological Engineering & Computing, 2020)
To explore the mechanical mechanism and provide preoperative planning basis for transtrochanteric rotational osteotomy (TRO) procedure, a joint-preserving procedure for osteonecrosis of the femoral head. Eleven TRO finite element femurs with the most common types of necrosis were analyzed under multi-loading conditions. Thereafter, we made a comprehensive evaluation by considering the anatomy characters, daily activities, and risk indicators contain necrosis expansion trend, necrotic blood supply pressure, and the risk of fracture. The risk of fracture (ROF) is the lowest when standing on feet and increases gradually during normal walking and walking upstairs and downstairs. Compared with posterior rotation, rotating forward keeps more elements at low risk. Additionally, the correlation analysis shows it has a strong negative correlation ( R 2 = 0.834) with the average modulus of the roof. TRO finally decreased the stress and energy effectively. However, the stress and strain energy arise when rotated posteriorly less than 120°. The comprehensive evaluation observed that rotating forward 90°could reduce the total risks to 64%. TRO is an effective technique to prevent collapse. For the anterior and superior large necrosis, we recommend to rotate forward 60° to 90° (more efficient) or backward 180°. The methodology followed in this study could provide accurate and personalize preoperative planning.

Mesozoic contraction deformation in the Yanshan and northern Taihang mountains and its implications to the destruction of the North China Craton - ChangHou Zhang; ChengMing Li; HongLing Deng; Yang Liu; Lei Liu; Bo Wei; HanBin Li; Zi Liu (Science China Earth Sciences, 2011)

A negative regulatory role for auxin in sulphate deficiency response in Arabidopsis thaliana - Hanbin Dan; Guohua Yang; Zhi-Liang Zheng (Plant Molecular Biology, 2006)